Burden of Caregiving on Informal Caregivers of Stroke Survivors in the Western Region - Okai, R. (University of Ghana, 2019)
Background: Stroke is a life-changing event which leaves the stroke survivors with varied degrees of disability requiring a lot of assistance from their informal caregivers who require substantial amounts of uncompensated time and energy to carry out their activities of daily living over a prolonged duration of time. The informal caregivers are therefore exposed to physical, psychological, social and financial problems, commonly reported as burden which affects their quality of life and may further compromise the stroke survivor’s recovery. Objectives: This study sought to give a deeper understanding of the burden of caregiving on informal caregivers of stroke survivors and the possible factors that contribute to the burden. Method: This facility based cross sectional study involved 118 pairs of stroke survivors and their informal caregivers over a 2 month period. Structured questionnaires were used to obtain quantitative data on socio-demographic and background characteristics, caregiver burden and level of disability whiles focus group discussion was used to obtain qualitative data. Descriptive analysis was done for socio-demographic data whiles Chi-square and logistic regression were used for inferential analysis at a significance level of p<0.05 and 95% confidence interval. Recorded discussions were transcribed verbatim and analysed by content thematic analysis. Results: One hundred and eighteen (118) pairs of informal caregivers and stroke survivors were surveyed in this study. Prevalence of caregiving burden was 74.6%, 66.9%, 63.6%, and 51.7% in the financial, physical, psychological and social domains respectively. Caregiving burden was significantly (p≤0.05) influenced by caregiver’s sex, number of tasks performed, level of stroke survivor’s disability, caregiver’s level of income, presence of comorbidities, employment status of caregiver and infrastructure at the physiotherapy department. Conclusion: A greater proportion of the informal caregivers reported to be burdened, with high moderate-severe burden in the financial domain. Caregiver factors; sex, number of tasks performed, employment status, level of income, comorbidities, stroke survivor factors; level of disability, comorbidities and health care facility factors; infrastructure at the physiotherapy facility contributed to the burden of care. These findings suggest the need for further research focused on the needs of informal caregivers and interventions to address their challenges.
MPH.
Keywords: Stroke; Informal Caregivers; Western Region